HUBUNGAN MEDIA SOSIAL DAN GAME ONLINE DENGAN PERILAKU BELAJAR PADA MATA PELAJARAN AKIDAH AKHLAK SISWA DI MADRASAH ALIYAH NEGERI 3 KOTA JAMBI - Irliadurrah, Marshanda Putri; Risnita; Darma Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the relationship between social media and online gameuse and student learning behavior in the Aqidah Akhlak (Islamic Creed) subject atMAN 3 Jambi City. The study used a quantitative approach with correlationalmethods. The sample consisted of 251 students selected using proportionaterandom sampling. Data were collected through a questionnaire based onindicators for each variable and analyzed using product-moment correlation andmultiple correlation. The results showed a positive and significant relationshipbetween social media use and learning behavior (R = 0.4445; KD = 19.75%) andbetween online games and learning behavior (R = 0.4627; KD = 21.41%).Simultaneously, both significantly influenced learning behavior (F-count = 64.717 >F-table = 3.03). This study concludes that social media and online games, as partof students' digital reality, have a strong relationship with learning behavior inAqidah Akhlak (Islamic Creed) learning. Therefore, the use of digital technologyneeds to be directed wisely to support character-based and spiritual education.